التحقق من التواقيع اليدوية باستخدام التوابع الإحصائية لصورة التوقيع - ساعي, مريم محمد; حجازية, محمد مصطفى; مريشة, رلى (Latakia University Journal -Engineering Sciences Series, 2014)
يقترح البحث طريقة جديدة تهدف إلى التحقق من صورة التوقيع اليدوي لشخص ما، وتحديد فيما إذا كان التوقيع يعود لهذا الشخص أو أنه توقيع مزور. وتم ذلك بالاعتماد على استخلاص سمات هندسية من صورة التوقيع الموجودة في قاعدة البيانات وإجراء عمليات إحصائية رياضية عليها كطريقة للتحقق من توقيع هذا الشخص. تم استخلاص السمات من صورة التوقيع على مراحل متعددة حيث تم تحويل صورة التوقيع من الصيغة الرمادية إلى الصيغة الثنائية ثم استخلاص الخصائص الإحصائية للتوقيع الأصلي وهي القيم الأكبر بين القيم الأكثر تكراراً في إحداثيات الواحدات التي تحدد شكل التوقيع، بالإضافة لعدد الواحدات التي تحدد شكل التوقيع، ثم تم تحديد مجالين للقيم المقبولة للتوقيع الأصلي. وبنفس الاسلوب ويتم استخلاص السمات الإحصائية للتواقيع المزورة واختبارها إذا كانت تنتمي إلى مجال القيم المقبولة المحدد. كما يتضمن البحث مقارنة لنتائج الطريقة المقترحة مع الطرق السابقة في هذا المجال. تم اختبار الطريقة المقترحة باستخدام قاعدة البيانات مكونة من16200 توقيع موزعة على 300 شخص، وكنتيجة لذلك تم التحقق بنسبة جيدة من صورة التوقيع اليدوي. This research suggests a new method that aims to verify the manual signature image which is written by person, and specify whether this signature back to this person or that forged signature. This was done by extracting geometric features of the signature image and applying statistical functions on them as a way to verify the signature of that person. The features from the signature image have been extracted on many stages, so a signature image has been transformed from the gray scale to binary format, and then extracting the statistical features from the original signature image which is the maximum value from the most repeated values in the ones' coordination line that determine the signature shape, in addition to the number of ones which also determine the signature shape. Finally two ranges have been identified for the values accepted for original signature image. By the same way, statistical features have been extracted from the foreign signature image and tested if they aggregate within the specified domain of acceptable values. This research also includes the results of the proposed approach that compared with the previous methods in this scope. The proposed method has been tested to the data base consisting of 16200 signatures back to 300 persons, and as a result the signature image has been verified with a good percentage.